Export Stages and Export Barriers: Revisiting Traditional Export Development. (22nd July 2015) - Kahiya, Eldrede T.; Dean, David L.
Abstract : This study revisits the stage model dialogue by testing seven hypotheses on the relationship between stages of export development and the influence of export barriers. Empirical data are based on a sample of 145 New Zealand firms, and the analysis combines a six‐stage framework with an illustrative list of barriers, while going a step further than previous research by examining the effect of covariates. Empirical results demonstrate that resource constraints, marketing barriers, knowledge and experience barriers, and export‐procedure barriers are "export stage dependent." However, regarding export‐stage‐dependent barriers, differences exist only when we compare the early to the very advanced stages of development. These results also refute the grand hypothesis, which suggests an inverse relationship between export stages and the influence of export barriers. While the stage model typology still provides a practicable basis for need‐based segmentation, it does not capture completely the heterogeneity associated with the middle stages. © 2015 Wiley Periodicals, Inc.